Defective transport of Sindbis virus glycoproteins in End4 mutant Chinese hamster ovary cells. - Presley, J F (1991)
Mutant V.24.1, a temperature-sensitive derivative of Chinese hamster ovary cells, defines the End4 complementation group of mutants selected for resistance to protein toxins and has defective lysosomes at the restrictive temperature (P. A. Colbaugh, M. Stookey, and R. K. Draper, J. Cell Biol. 108:2211-2219, 1989). We have investigated the biosynthesis of Sindbis virus envelope glycoproteins in V.24.1 cells. When the cells were infected at the restrictive temperature, the envelope glycoproteins E1 and E2 were undetectable on the cell surface and proteolytic processing of the precursor protein pE2 to envelope protein E2 did not occur. Protein retained intracellularly was sensitive to endoglycosidase H and, by immunofluorescence localization, appeared to accumulate in the endoplasmic reticulum. We conclude that the genetic defect in V.24.1 cells impairs the transport of Sindbis virus glycoproteins, apparently at the level of export from the endoplasmic reticulum.